Analysis of the Influence of Social Media Marketing on Purchase Intention with Customer Trust as a Mediating Variable at Relasi Coffee Pematangsiantar - Juntri Julianus Sinurat; Hengki Mangiring Parulian Simarmata; Novendra A. Sinaga (Journal of Management and Business Analytics, 2026)
This study discusses the influence of Social Media Marketing on Purchase Intention with Customer Trust as a mediating variable in the Pematangsiantar coffee relationship. The purpose of this study is to determine the influence of social media marketing on purchase intention with customer trust as a mediating variable in the Pematangsiantar coffee relationship. This type of research uses a quantitative method, the population in this study is all customers in the coffee relationship with a sample of 300 people. Data collection techniques use interviews, observations, and questionnaires that have been tested for validity and reliability. The data analysis technique used to answer the hypothesis is multiple linear regression. The results of this study indicate that there is an influence of social media marketing on purchase intention with customer trust as a mediating variable in the Pematangsiantar coffee relationship partially. Evidenced by the Tcount < Ttable value for social media marketing on purchase intention of 0.000 < 0.05. The Tcount < Ttable value for social media marketing on customer trust of 0.001 < 0.05. The calculated T value < T table for purchase intention on customer trust is 0.000 < 0.05. The calculated F value > F table for the influence of social media marketing on purchase intention mediated by customer trust is 756.312 > 3.02.